Legal Study in Packaged Food Products Without Raw Material Labels from the Perspective of Consumer Protection (Literature Review) - Hanjaya, Resyah Prima; Harmono, Harmono (Jurnal Legisci, 2024)
Snack foods produced by the lower middle class in our vicinity lack raw material labeling as mandated by BPOM RI. This article's findings seek to analyze unlabeled packaged food goods from the consumer protection standpoint. The literature review methodology employs resources from diverse publications published in various journals and obtained from the internet. The analysis concludes that Basreng Lembayun, Raja Snack glass chips, Chocomary thin Chocolate Matcha, and Fruit Chips lack composition labels, net weight, and expiration dates, infringing on consumer rights. It is essential to enhance the realization of consumer rights to provide security, access to product information, the ability to be heard, and the right to participate in decision-making.